Perbedaan Efektivitas Edukasi Media Booklet dan Video terhadap Pengetahuan Gizi Seimbang Pendamping Anak Autism Spectrum Disorder di Wilayah Jabodetabek: The Difference in Effectiveness of Booklet and Video Media Education on Balanced Nutrition Knowledge of Caregivers for Children with Autism Spectrum Disorder in Jabodetabek Area - Putri, Tiara Kumala; Simanungkalit, Sintha Fransiske; Sianturi, Hendry Roris P; Nasrullah, Nanang (Universitas Airlangga, 2024)
Background: Children with Autism Spectrum Disorder (ASD) require adequate and proper balanced nutrition to support their growth, development, and to prevent nutritional problems. One of the factors influencing nutritional problems is the lack of knowledge among caregivers. Nutrition education can be applied to improve the knowledge of caregivers of children with ASD about balanced nutrition. The use of educational media in the form of booklet and video are considered effective. However, the differences in effectiveness between the two media needs to be analyzed. Objectives: To determine the differences in the effectiveness of booklet and video media education on the balanced nutrition knowledge among caregivers of children with ASD in the Jabodetabek area. Methods: This study used a quasi-experimental design with a two-group pre-test post-test design. The sample was caregivers of children with ASD in Jabodetabek area who met inclusion and exclusion criteria, totalling 60 people each in the control and experimental group. The sampling technique was cluster sampling with a research instrument in the form of a questionnaire. Data analysis was conducted using univariate analysis and bivariate analysis was conducted using Mann-Whitney test. Results: The Mann-Whitney test result showed that p-value 0.003 (p-value<0.05) indicating both booklet and video media were effective. The mean score in the video group was greater at 67.23, compared to the mean in the booklet group at 53.77. Conclusions: Nutritional education using video media is more effective in improving the balanced nutrition knowledge of caregivers of children with ASD compared to booklet.